2009
DOI: 10.1097/01.asw.0000305452.79434.d9
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Negative Pressure Wound Therapy for Postsurgical Patients in Long-term Acute Care

Abstract: Postsurgical LTAC patients who were treated by NPWT/ROCF had a more accelerated rate of wound closure, compared with patients treated with advanced moist wound-healing therapy. These results suggest that, for this patient group, NPWT/ROCF may be more clinically effective in reducing wound volume, compared with advanced moist wound healing. Furthermore, the lower cost per cubic centimeter volume reduction suggests that NPWT/ROCF produces a more favorable cost-effective solution. Therefore, it is important when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 10 publications
1
24
0
4
Order By: Relevance
“…The authors concluded that NPWT achieves lower overall costs and superior outcomes compared to standard treatment for severe pressure ulcers [9,10]. Other researchers have concluded that NPWT is cost-effective compared to standard treatment in retrospective chart reviews [11] and comparative case-studies [12]. The results of these studies are highly uncertain and generalisability is limited by the heterogeneity of patients receiving NPWT [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that NPWT achieves lower overall costs and superior outcomes compared to standard treatment for severe pressure ulcers [9,10]. Other researchers have concluded that NPWT is cost-effective compared to standard treatment in retrospective chart reviews [11] and comparative case-studies [12]. The results of these studies are highly uncertain and generalisability is limited by the heterogeneity of patients receiving NPWT [6].…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies are highly uncertain and generalisability is limited by the heterogeneity of patients receiving NPWT [6]. Additionally, most cost-effectiveness studies have focused on the treatment of chronic, difficult-to-heal wounds [6,10,11]. NPWT is increasingly used prophylactically following surgery for high-risk clean wounds [13], particularly in obese patients at greater risk of developing SSIs [14].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews have been published, which summarize the efficacy and safety of NPWT for treatment of acute and chronic wounds. [1][2][3][4][5] Additional research has focused on cost, 6,7 gauze-based NPWT systems, 8 and the science behind the therapy, including the mechanism of action of vacuum assistance, 9,10 tissue pressure, 11 granulation tissue formation, 12 microvascular blood fl ow, 13 and intermittent versus continuous pressure. 14 However, Gregor and colleagues 15 reported a sy stematic review and meta-analysis of randomized controlled and nonrandomized clinical trials, comparing conventional therapy to NPWT in acute and chronic wounds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5 In addition, NPWT seems effective in stimulating reapproximation of wound edges and granulating overexposed structures in the early stages of wound healing. 6 Recently, it has been found that NPWT can be applied at lower pressures (j75 mm Hg) than what was originally thought (j125 mm Hg). 7 Studies have shown that intermittent low pressure is more effective than continuous high pressure at increasing microvascular blood flow.…”
mentioning
confidence: 98%